Purchase decision: The role of product quality, brand image, and brand ambassador - Mohamed, Eissa Thabit (Universitas Ahmad Dahlan, 2024)
Purpose- This technological advancement has extended to the world of telecommunications. This can be proven by the presence of smartphones, which offer advantages in various ways. Each manufacturer tries influencing consumers to make purchases by relying on product excellence. Purchasing decisions are essential for every manufacturer regarding marketing their products. Many factors can influence consumer purchasing decisions. This study examines product quality, brand image, and brand ambassadors as antecedents of purchasing decisions. Design/Methodology/Approach- The respondents in this study were Asian iPhone users. Purposive sampling was used to choose the sample, obtaining 119 responses. Questionnaires were distributed to gather data, and Smart PLS was used for analysis. Validity, reliability, and hypothesis regression tests were the methods of data analysis that were used. Findings- Product quality that meets consumer desires and expectations, as well as the sacrifices that consumers make to obtain these products, can encourage consumer decisions to buy them. A positive brand image can also promote purchasing decisions because consumers feel that the product has proven reliable and is able to meet consumer expectations and desires. Brand ambassadors are also a driving factor in purchasing decisions because they can influence consumers by promoting products. Research Limitations/Implications- This study's limitation is that the research results only represent iPhone users in Asia, so the respondents' answers cannot represent all iPhone users in the world. In addition, the iPhone is one of the product lines produced by Apple Inc., so the results of this study are only limited to the iPhone product line; they cannot represent other product lines from Apple Inc. Originality/Value- Research on the factors influencing consumer purchasing decisions for iPhones in Asia is minimal. Similar studies only discuss iPhone product users in several Asian countries or users of other Apple Inc product lines.